The Effects of Ethanol Extract, Chayote (Sechium Edule (Jacq.) Swartz) Fraction and Juice on the High-density Lipoprotein Level in Male White Mice - Siahaan, Jekson Martiar; Anto, Endy Juli; Fauzi, Tengku Muhammad (Indonesian Journal of Medicine, 2021)
Background: Cholesterol imbalance occurs in Diabetes Mellitus, where high-density lipoprotein (HDL) levels are low and low-density lipoprotein (LDL) increases, where this imbalance results in the appearance of atherosclerosis. HDL has antiarterosclerotic potential so it needs to be targeted for therapy. One of the bioactive compounds that have this effect is found in chayote (Sechium edule (Jacq.) Swartz). This study aimed to examine the effects of ethanol extract, Chayote (Sechium Edule (Jacq.) Swartz) fraction and juice on the hdl level in male white miceSubjects and Method: A randomized controlled trial study was conducted to test HDL level in 54 male white rats of the Wistar strain (Rattus novergius sp.) after received ethanol extract, Chayote (Sechium Edule (Jacq.) Swartz) fraction and juice. The dependent variable was the HDL level. The independent variable was the variation in the dose of ethanol extract, fraction and Sechium edule (Jacq.) Swartz Juice. The data were analyzed using Anova test.Results: The treatment group induced by Streptozotocin 50 mg / kgBW + nicotinamide (120 mg/kgBW) + HFD and obtained ethanol extract of chayote fruit 150 mg / kgBW, orally had the highest average HDL levels compared to other groups (Mean = 17.31; SD = 3.14).Conclusion: The ethanol solvent found in the ethanol extract is better because it attracts biaoctive compounds so that it has a better effect than the ethyl acetate fraction and the n-hexane fraction.Conclusion: The ethanol solvent found in the ethanol extract is better because it attracts biaoctive compounds so that it has a better effect than the ethyl acetate fraction and the n-hexane fraction.Keywords: HDL, Flavonoid, Sechium edule (Jacq.) SwartzCorrespondence: Jekson Martiar Siahaan. Department of Physiology, Faculty of Medicine, Universitas Methodist Indonesia. Jl. Setia Budi Pasar II Tj. Sari, Medan 20132, North Sumatera. Email: jekson.siahaan.sked@gmail.comIndonesian Journal of Medicine (2021), 06(02): 145-151https://doi.org/10.26911/theijmed.2021.06.02.03